Titre-t-on sur le Net comme on titre sur papier - de l’évolution du titrage médiatique - Jereczek-Lipinska, Jereczek-Lipinska, Joanna (Studia Romanica Posnaniensia, 2005)
All media are equipped with a specific code of writing bus since always avenement of media causes the appearance of a language even of a technique of writing suitable for the media in question. Each one of these media forges its own technique of communication which continues besides to evolve just like changes its support. We propose to recall this evolution like perceiving the advent of the specific language through one of the elements essential of the media account of the newspaper industry and the cyberpress with knowing titration. It is a challenge by knowing that the Internet is not media like the others but a multi-media support, it thus includes all the media in one. Our objective is to define the stage to which the cybertitre in this evolutionary diagram is.